Director's Report of Research in Kansas 2017 - J. E. Minton (Kansas Agricultural Experiment Station Research Reports, 2018)
The 2017 Director’s Report of Research in Kansas includes a list of journal articles, station publications, and other published manuscripts from scientists in our departments, research-extension centers, and associated programs.
Keywords: Agriculture